Geoecologia de paisagem e planejamento ambiental da bacia hidrográfica do Alto Jacuí - Ziani, Patrícia (2022)
The main goal of this research is to offer indications for the environmental planning of Alto Jacuí's watershed, based on the definition of landscape units, aiming to contribute to the landuse planning of this landscape and the water resource management. To that end the following specific objectives were defined: carry out the studying area's inventory, identifying the physical, socioeconomic, ecologic, and cultural characteristics of the landscape; diagnose landscape units and existing environmental conflicts; systematize landscape units based on inventory and diagnosis; regionalize the Alto Jacuí's watershed into spatial management units. For that, this research is based on the methodological conceptions of Rodriguez (1994), Rodriguez e Silva (2013), Leal (1995), and Bovet e Ribas (1992), thus developing five steps: organization, inventory, diagnosis, prognosis, and propositions, associated with fieldwork realization in the study area. Among the results found stands out the identification of 8 landscape units through morphologic and structural data combination that allowed us to identify more or less homogenous areas in Alto Jacuí's watershed. It is hoped that the map of landscape units can serve as support for decision-making, going beyond the environmental planning, guiding other land-use planning public policies, for example, tourism and cultural interests, education, and socioeconomic system that adds up to a systemic landscape perspective, encouraging this land's endogenous development. It's understood that the present research consists of a solid base for planning, management, and decision-making at local and regional levels, serving as a base for future works aiming to improve geo-ecological studies, shaping itself as an important knowledge and planning instrument for the area's landscape, providing the counties an embracing view of the landscape elements, subsidizing the land-use and environmental planning from short to long-term deadlines of ground usage and coverage.